2017
DOI: 10.1371/journal.pone.0177466
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of white matter connectivity in cortex maturation

Abstract: The maturation of the cortical gray matter (GM) and white matter (WM) are described as sequential processes following multiple, but distinct rules. However, neither the mechanisms driving brain maturation processes, nor the relationship between GM and WM maturation are well understood. Here we use connectomics and two MRI measures reflecting maturation related changes in cerebral microstructure, namely the Apparent Diffusion Coefficient (ADC) and the T1 relaxation time (T1), to study brain development. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 94 publications
1
25
0
Order By: Relevance
“…With new emerging MRI techniques, better characterization of EoP now became possible and opens new understanding, such as functional connectivity, diffusion tensor imaging, fractional anisotropy measures and fiber tractography, and automated segmentation techniques for volume determination and growth (Ball et al, 2013;Gozdas et al, 2018;Schneider et al, 2018;Duerden et al, 2019;Jakab et al, 2019). The most prominent findings of EoP in VPT are (1) decreased global brain volume due to white (WM) and gray matter reduction [(GM); cortical GM as well as deep nuclear GM], (2) hydrocephalus ex vacuo (CSF), and (3) connectivity impairment (Dubois et al, 2008;Ball et al, 2013;Chau et al, 2013;Kidokoro et al, 2013;Friedrichs-Maeder et al, 2017;Gozdas et al, 2018;Duerden et al, 2019;Jakab et al, 2019).…”
Section: Encephalopathy Of the Prematurity In Humans And Evidence Of mentioning
confidence: 99%
“…With new emerging MRI techniques, better characterization of EoP now became possible and opens new understanding, such as functional connectivity, diffusion tensor imaging, fractional anisotropy measures and fiber tractography, and automated segmentation techniques for volume determination and growth (Ball et al, 2013;Gozdas et al, 2018;Schneider et al, 2018;Duerden et al, 2019;Jakab et al, 2019). The most prominent findings of EoP in VPT are (1) decreased global brain volume due to white (WM) and gray matter reduction [(GM); cortical GM as well as deep nuclear GM], (2) hydrocephalus ex vacuo (CSF), and (3) connectivity impairment (Dubois et al, 2008;Ball et al, 2013;Chau et al, 2013;Kidokoro et al, 2013;Friedrichs-Maeder et al, 2017;Gozdas et al, 2018;Duerden et al, 2019;Jakab et al, 2019).…”
Section: Encephalopathy Of the Prematurity In Humans And Evidence Of mentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) studies have also shown that the advancement of grey and white matter in the fetus is inter‐related, and highly dependent on the integrity and complexity of the underlying axonal circuitry within the white matter tracts (Friedrichs‐Maeder et al . ). As discussed below, preterm birth disrupts the establishment of the neural connectivity framework, and this impacts on the development and efficiency of sleep.…”
Section: Introductionmentioning
confidence: 97%
“…The network also supports molecular transport, including molecules and organelles required for neurotransmission and metabolism [50]. Altogether, the architecture of this white matter "connectome" fundamentally shapes the development and function of the brain [28].…”
Section: Introductionmentioning
confidence: 99%